Simulate the induction heating process with the 3D coil design - Phạm Sơn Minh; Trần Văn Trọn (Journal of Technical Education Science, 2013)
In the field of dynamic mold temperature control for injection molding process, the induction heating method has many advantages as high heating rate, low energy consumption and reduced environmental pollution. In this research, the simulation method was used for determining the heating rate and the temperature distribution of the 3D coil induction heating. The result shows that the heating rate can reach to 30oC/s at the mold surface, and the temperature distribution has a clear improvement when we compare with the other coil design. With the 3D coil design, the higher temperature appears at the center of the mold plate with a rectangular area.